Preparation method of lignin sodium sulfonate / chitosan high mesoporous nitrogen and sulfur co-doped porous carbon-based supercapacitor electrode material
By using a porous carbon material with a cross-linked network structure formed by sodium lignosulfonate and chitosan, the problems of long preparation time and poor energy storage effect in the existing technology have been solved, and a supercapacitor electrode material with high specific surface area and excellent electrochemical performance has been realized.
Patent Information
- Application Number
- CN202310980492.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-08-04
AI Technical Summary
Existing methods for preparing supercapacitor electrode materials suffer from problems such as long hydrothermal and carbonization times, high energy consumption, insufficient heteroatom doping, and inadequate pore structure and specific surface area, resulting in poor energy storage performance.
A highly mesoporous nitrogen- and sulfur co-doped porous carbon material was prepared by assembling nanospheres with sodium lignosulfonate and chitosan, and then carbonized with supercritical CO2 and high temperature. The nitrogen and sulfur atoms of biomass itself were used to improve the electrochemical performance.
The prepared porous carbon material has a high specific surface area and excellent electrochemical performance, exhibiting a high specific capacitance of 263 F/g and a cycle stability of 97%, making it suitable for supercapacitor electrode materials.
Smart Images

Figure CN117012557B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of supercapacitor electrode material preparation, and relates to a method for preparing a nitrogen and sulfur co-doped porous carbon-based supercapacitor electrode material of sodium lignosulfonate / chitosan with high mesopority. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Supercapacitors have shown promising application prospects in the energy storage field due to their significant advantages in high power density, fast charge / discharge rates, and long cycle life. As a high-performance dense energy source, its performance is mainly determined by the electrode materials. Ideal carbon-based electrode materials possess rich pore structures, high specific surface areas, stable chemical properties, and low cost, making them suitable for large-scale production.
[0004] To enrich the pore structure, Chinese patent CN 110862077A discloses a method for preparing hierarchical porous carbon materials rich in mesopores for supercapacitors. This method involves mixing lignin, sericin, and sulfuric acid solution, ultrasonically dispersing the mixture, and then hydrothermally reacting the resulting suspension at 170–190°C for 16–20 hours. The resulting product is then mixed with an activator, and the activation reaction is carried out at a heating rate of 1–10°C / min to 700–900°C for 1–3 hours; the soaking time is 5–10 hours. The mixture is then soaked in hydrochloric acid solution, washed until neutral, and filtered to obtain the porous carbon material. However, this method involves long hydrothermal and carbonization times, high energy consumption, and significant product volatilization at high temperatures, resulting in low product yield. For example, Chinese patent CN 109767927A discloses a method for preparing high-performance nitrogen-doped biomass porous carbon for supercapacitors. This method involves adding biomass to a mixed solution of concentrated alkali and hydrogen peroxide for oxidative hydrolysis, followed by adding urea or thiourea for swelling treatment, freeze-drying, and carbonization to obtain nitrogen-doped biomass porous carbon. However, it lacks heteroatom sulfur doping, and its energy storage performance still needs improvement. Similarly, Chinese patent CN115285991A discloses a method for generating hierarchical porous carbon based on the self-assembly of biomass derivatives and its application, but its preparation method is complex, and the mesopore volume and specific surface area still need improvement. Summary of the Invention
[0005] To address the aforementioned problems, this invention provides a method for preparing a nitrogen- and sulfur-co-doped porous carbon-based supercapacitor electrode material composed of sodium lignosulfonate / chitosan with high mesoporous structure. This invention utilizes nanospheres formed from chitosan and sodium lignosulfonate to assemble a cross-linked network structure, which promotes the entry of activators and the escape of gases during carbonization, thereby forming a highly mesoporous carbon material with a high specific surface area. Simultaneously, by utilizing the heteroatoms N and S inherent in biomass, superior electrochemical performance is achieved without the introduction of other heteroatoms, making it suitable for use as a supercapacitor electrode material.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing a nitrogen- and sulfur-co-doped porous carbon-based supercapacitor electrode material of sodium lignosulfonate / chitosan, comprising:
[0008] Sodium lignosulfonate solution and chitosan solution were mixed evenly, then a crosslinking agent was added, the reaction was carried out, the solid product was collected, and supercritical CO2 drying was performed to obtain lignocross chitosan material.
[0009] The lignin-crosslinked chitosan material was ground, activated with KOH and urea, carbonized, acid-washed, and dried to obtain nitrogen and sulfur co-doped lignin porous carbon material.
[0010] The mass ratio of sodium lignosulfonate to chitosan is 1:1.
[0011] This invention utilizes environmentally friendly raw materials and employs methods such as CO2 supercritical drying, one-step activation, and high-temperature carbonization to prepare a nitrogen- and sulfur-co-doped porous carbon-based supercapacitor electrode material composed of sodium lignosulfonate / chitosan with high mesoporous structure.
[0012] Lignin is widely found in the cell walls of higher plants and is a renewable biomass resource; chitosan is a nitrogen-containing polysaccharide, a natural bioactive substance. The intermolecular forces between lignin and chitosan, including hydrogen bonds, electrostatic interactions, and van der Waals forces, provide a good chemical basis for the self-assembly of these two natural polymers into composite materials. In this invention, the lignin-crosslinked chitosan material retains its original crosslinked network morphology even after high-temperature carbonization at 800℃. Activation breaks down the original three-dimensional structure of the biomass-based carbon material, removing the limitations of the pore structure. The high-performance sodium lignin sulfonate / chitosan highly mesoporous nitrogen- and sulfur-doped porous carbon for supercapacitors prepared using the method of this invention has a specific surface area as high as 2,876 m². 2 / g, pore volume 1.52cm 3The average pore size distribution is 2.1 nm. In a three-electrode system with Hg / HgO as the reference electrode and a platinum sheet as the counter electrode, the specific capacitance is 263 F / g at 1 A / g in 1 M potassium hydroxide solution, exhibiting excellent specific capacitance and cycle stability.
[0013] In a second aspect, the present invention provides a nitrogen- and sulfur co-doped porous carbon-based supercapacitor electrode material of sodium lignosulfonate / chitosan prepared by the above method.
[0014] A third aspect of the present invention provides the application of the above-mentioned sodium lignosulfonate / chitosan highly mesoporous nitrogen and sulfur co-doped porous carbon-based supercapacitor electrode material in the preparation of supercapacitors.
[0015] Beneficial effects of the present invention
[0016] (1) Chitosan is a nitrogen-containing polysaccharide natural organic polymer. This invention utilizes the abundant nitrogen element in chitosan, which not only improves the chemical inertness of the material surface and provides active sites that can participate in catalytic reactions for nitrogen-doped carbon materials, but also changes the electronic structure of the carbon surface and improves its conductivity. Therefore, it increases the specific capacitance of carbon materials. Under industrial production conditions, it avoids heavy metal pollution to the environment, and chitosan is widely distributed and suitable for mass production.
[0017] (2) Sodium lignosulfonate is used as a carbon and sulfur precursor. Sulfur atom doping can effectively improve the energy storage of porous carbon, while chitosan is used as a nitrogen precursor. Nitrogen atom doping improves the electron distribution on the carbon surface and enhances the electron-donating ability of carbon materials.
[0018] (3) The hierarchical porous carbon material prepared by this invention has a regular structure, a large specific surface area and adsorption capacity, a well-developed internal pore structure and good chemical stability; when it is prepared as an electrode material, it will have excellent specific capacitance and the structure remains stable after long-term cycling, which meets the ideal material for supercapacitor electrodes.
[0019] (4) Compared with patent CN115285991A, this invention utilizes nanospheres formed by chitosan and sodium lignosulfonate to assemble a cross-linked network structure, which promotes the entry of activator and the escape of gas during carbonization, thereby forming a high-mesoporous carbon material with a high specific surface area (specific surface area can reach 2876 m²). 2 / g, with a mesoporous volume fraction as high as 95%; at the same time, by utilizing the heteroatoms N and S in biomass itself, superior electrochemical performance is obtained without the introduction of other heteroatoms (exhibiting a high specific capacitance of 263 F / g at 1 A / g, with a capacitance retention of 97% after 10,000 cycles. At a power density of 600 W / kg, its energy density is 16.8 Wh / kg), which can be used as an electrode material for supercapacitors, and the preparation method is also simpler. Attached Figure Description
[0020] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. Exemplary embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0021] Figure 1 The following are physical property characterization diagrams of the nitrogen and sulfur co-doped porous carbon materials in Example 2, where (a) is a SEM image of the lignin / chitosan composite; (b) is a SEM image of the mesoporous carbon material; (c) is the adsorption isotherm of the mesoporous carbon material; and (d) is the pore size distribution diagram of the mesoporous carbon material.
[0022] Figure 2 This is a cyclic voltammetry diagram of the electrodes for the supercapacitor at different scan rates in Example 2.
[0023] Figure 3 This is a charge-discharge curve of the electrodes for the supercapacitor under different current densities in Example 2. Detailed Implementation
[0024] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0025] A sodium lignosulfonate / chitosan highly mesoporous nitrogen- and sulfur-co-doped porous carbon-based supercapacitor electrode material, comprising:
[0026] Step S1: Preparation of lignin-crosslinked chitosan material
[0027] Sodium lignin sulfonate was dissolved in deionized water and stirred until completely dissolved; chitosan was dissolved in acetic acid solution and stirred until completely dissolved; the two solutions were mixed, a crosslinking agent was added, stirred, centrifuged, and dried to obtain lignin-crosslinked chitosan material.
[0028] Step S2: Highly mesoporous nitrogen- and sulfur co-doped porous carbon materials
[0029] The lignin-crosslinked chitosan material obtained in step S1 is ground, activated, carbonized, washed with hydrochloric acid, and then dried to obtain a highly mesoporous nitrogen and sulfur co-doped porous carbon material.
[0030] Lignosulfonates play a crucial role as a source of sulfur and a carbon source for the formation of amorphous carbon scaffolds and carbides. Chitosan is used as a nitrogen source for nitrogen doping to produce carbon, which can effectively induce a large number of defects in the carbon microstructure, increase the specific surface area to accommodate more ions, and improve the electrochemical performance of carbon materials.
[0031] In some embodiments, the pH of the acetic acid solution is 3.
[0032] In some embodiments, the crosslinking agent is a mixture of anhydrous sodium sulfate, formaldehyde, sulfuric acid, and water. Sulfuric acid provides the acidic conditions, formaldehyde performs the crosslinking action, and the remaining hexachlorocyclohexane is decomposed by anhydrous sodium sulfate. The resulting lignin-crosslinked chitosan material has a large specific surface area and adsorption capacity, a well-developed internal pore structure, and good chemical stability.
[0033] In some embodiments, the sodium lignosulfonate solution is an aqueous solution of sodium lignosulfonate with a concentration of 0.3–0.6 g / ml.
[0034] In some embodiments, the chitosan solution is an acetic acid solution of chitosan with a concentration of 0.3–0.6 g / ml.
[0035] In some embodiments, the mass ratio of lignin / chitosan complex:KOH:urea is 1:1:0 to 1, preferably 1:10; 1:1:0.5 and 1:1:1.
[0036] In some embodiments, the carbonization conditions are: temperature 750–800°C and holding time 1–2 hours.
[0037] In some embodiments, the carbonization is carried out under nitrogen protection at a heating rate of 5–8 °C / min. -1 .
[0038] In some embodiments, the concentration of the hydrochloric acid solution is 1–1.5 mol / L. -1 ;
[0039] In some embodiments, the drying is vacuum drying at a temperature of 80–85°C.
[0040] The present invention will be further described in detail below with reference to specific embodiments. It should be noted that the specific embodiments are explanations of the present invention and not limitations thereof.
[0041] Example 1
[0042] Weigh 5g of sodium lignosulfonate and dissolve it in 150ml of deionized water; weigh 5g of chitosan and dissolve it in 150ml of acetic acid aqueous solution with pH=3; stir overnight at room temperature; while stirring, add 50ml of chitosan solution dropwise to 50ml of sodium lignosulfonate solution, and stir for 30min at room temperature to obtain a mixture; add sulfuric acid (6.80ml), formaldehyde (6.63ml), and anhydrous sodium sulfate (15g) to 20mL of deionized water, and stir continuously for 10min at room temperature to prepare a crosslinking solution; add the crosslinking solution to the mixture using a syringe, and stir the resulting solution for another 30min; centrifuge at 8000r / min for 10min, add deionized water and wash repeatedly to obtain the complex; dry the complex using a supercritical CO2 dryer to obtain a powder.
[0043] The lignin / chitosan complex, potassium hydroxide, and urea were mixed in a mass ratio of 1:1:0. 40 mL of deionized water was added, and the mixture was sonicated for 1 h. The mixture was then dried overnight in an oven at 105 °C. The solid was ground into powder and placed in an inert atmosphere for carbonization at 800 °C for 2 h. The product was then washed in 1 mol / L hydrochloric acid, followed by water washing until neutral. After filtration and vacuum drying, nitrogen and sulfur co-doped porous carbon electrode material was obtained.
[0044] Example 2
[0045] Weigh 5g of sodium lignosulfonate and dissolve it in 150ml of deionized water; weigh 5g of chitosan and dissolve it in 150ml of acetic acid aqueous solution with pH=3; stir overnight at room temperature; while stirring, add 50ml of chitosan solution dropwise to 50ml of sodium lignosulfonate solution, and stir for 30min at room temperature to obtain a mixture; add sulfuric acid (6.80ml), formaldehyde (6.63ml), and anhydrous sodium sulfate (15g) to 20mL of deionized water, and stir continuously for 10min at room temperature to prepare a crosslinking solution; add the crosslinking solution to the mixture using a syringe, and stir the resulting solution for another 30min; centrifuge at 8000r / min for 10min, add deionized water and wash repeatedly to obtain the complex; dry the complex using a supercritical CO2 dryer to obtain a powder.
[0046] The lignin / chitosan complex, potassium hydroxide, and urea were mixed in a mass ratio of 1:1:0.5, 40 mL of deionized water was added, and the mixture was sonicated for 1 h. The mixture was then dried overnight in an oven at 105 °C. The solid was ground into powder and placed in an inert atmosphere for carbonization at 800 °C for 2 h. The product was then washed in 1 mol / L hydrochloric acid, followed by water washing until neutral, filtration, and vacuum drying to obtain nitrogen and sulfur co-doped porous carbon electrode material.
[0047] Example 3
[0048] Weigh 5g of sodium lignosulfonate and dissolve it in 150ml of deionized water; weigh 5g of chitosan and dissolve it in 150ml of acetic acid aqueous solution with pH=3; stir overnight at room temperature; while stirring, add 50ml of chitosan solution dropwise to 50ml of sodium lignosulfonate solution, and stir for 30min at room temperature to obtain a mixture; add sulfuric acid (6.80ml), formaldehyde (6.63ml), and anhydrous sodium sulfate (15g) to 20mL of deionized water, and stir continuously for 10min at room temperature to prepare a crosslinking solution; add the crosslinking solution to the mixture using a syringe, and stir the resulting solution for another 30min; centrifuge at 8000r / min for 10min, add deionized water and wash repeatedly to obtain the complex; dry the complex using a supercritical CO2 dryer to obtain a powder.
[0049] The lignin / chitosan complex, potassium hydroxide, and urea were mixed in a mass ratio of 1:1:1, 40 mL of deionized water was added, and the mixture was sonicated for 1 h. The mixture was then dried overnight in an oven at 105 °C. The solid was ground into powder and placed in an inert atmosphere for carbonization at 800 °C for 2 h. The product was then washed in 1 mol / L hydrochloric acid, followed by water washing until neutral, filtration, and vacuum drying to obtain nitrogen and sulfur co-doped porous carbon electrode material.
[0050] Comparative Example 1
[0051] The difference from Example 2 is that the crosslinking solution contains only formaldehyde.
[0052] The microstructure of the samples was characterized using a scanning electron microscope (Hitachi Regulus 8220); the specific surface area and pore structure of the samples were tested using a fully automated gas adsorption analyzer; and the electrochemical tests were performed using an electrochemical workstation.
[0053] The electrochemical workstation (CHI660E) employed a three-electrode system for all tests. The working electrode preparation process was as follows: Nitrogen- and sulfur-doped lignin porous carbon nanomaterials, carbon black, and polytetrafluoroethylene emulsion were mixed in a mass ratio of 8:1:1, ultrasonically pulverized, and coated in small batches onto 1cm × 1cm nickel foam. After drying and pressing, the working electrode was obtained. The reference electrode was an Hg / HgO electrode, and the counter electrode was a platinum sheet electrode. Cyclic voltammetry was performed within a voltage window of -1 to 0.2V at a scan rate of 10–100 mV / s. Constant DC charge-discharge curves were performed within a voltage window of -1 to 0.2V at a current density of 0.5–30.0 A / g.
[0054] Since the carbon material obtained in Example 2 has the most ideal specific capacitance, the material prepared by the method in Example 2 was tested and subjected to electrochemical tests. Figures 1-3 .
[0055] Table 1 compares the electrochemical performance of the nitrogen- and sulfur-co-doped porous carbon materials prepared in the above embodiments.
[0056] Table 1 lists the electrochemical performance of Examples 1-3.
[0057]
[0058]
[0059] As shown in Table 1, the highly mesoporous nitrogen- and sulfur-doped porous carbon electrode material prepared by a simple activation method (Example 2, lignin / chitosan composite: KOH: urea = 1:1:0.5) exhibits high specific capacitance and cycling stability. This is mainly because the appropriate doping ratio of KOH and urea can create a rich pore structure, providing a larger specific surface area, which is beneficial to improving the electrochemical performance of the composite electrode material. The specific surface area of Example 2 is as high as 2,876 m². 2 / g, pore volume 1.52cm 3 / g, with an average pore size distribution of 2.1nm. Meanwhile, a comparison between Comparative Example 1 and Example 2 shows that the lignin-crosslinked chitosan material formed using a crosslinking agent (composed of anhydrous sodium sulfate, formaldehyde, and sulfuric acid) has a larger specific surface area and adsorption capacity, a well-developed internal pore structure, and superior electrochemical performance.
[0060] Figure 1 The highly mesoporous nitrogen- and sulfur-doped porous carbon prepared in Example 2 is an example of this. Figure 1 Image (a) shows an SEM image of the lignin / chitosan complex, revealing a cross-linked network structure. Figure 1 Image (b) shows an SEM image of the mesoporous carbon material, revealing pore structures of different sizes. Figure 1 (c) shows the adsorption isotherm of the mesoporous carbon material, which exhibits a type IV isotherm and a slight hysteresis loop when the relative pressure (P / P0) is above 0.5, indicating the presence of a large number of mesopores. Figure 1 The middle (d) diagram shows the pore size distribution of the mesoporous carbon material, which exhibits a sharp peak at 1.8-3 nm.
[0061] Figure 2 These are cyclic voltammograms of the supercapacitor electrodes at different scan rates in Example 2. As the scan rate increases, these curves exhibit a more ideal rectangular shape, indicating good electrochemical performance.
[0062] Figure 3The graphs show the charge-discharge curves of the supercapacitor electrodes under different current densities in Example 2. All curves exhibit an approximately isosceles triangle shape, indicating that the electrodes possess excellent reversibility and good coulombic efficiency.
[0063] Therefore, Example 2 exhibits a high specific capacitance of 263 F / g at 1 A / g, with a capacitance retention of 97% after 10,000 cycles. Its energy density is 16.8 Wh / kg at a power density of 600 W / kg.
[0064] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a nitrogen- and sulfur-co-doped porous carbon-based supercapacitor electrode material of sodium lignosulfonate / chitosan, characterized in that, include: Sodium lignosulfonate solution and chitosan solution were mixed evenly, then a crosslinking agent was added, the reaction was carried out, the solid product was collected, and supercritical CO2 drying was performed to obtain lignocross chitosan material. The crosslinking agent is a mixture of anhydrous sodium sulfate, formaldehyde, sulfuric acid and water; The lignin-crosslinked chitosan material was ground, activated with KOH and urea, carbonized, acid-washed, and dried to obtain a highly mesoporous nitrogen and sulfur co-doped porous carbon material; the mass ratio of lignin / chitosan complex:KOH:urea was 1:1:0~1. The mass ratio of sodium lignosulfonate to chitosan is 1:
1.
2. The preparation method of the nitrogen- and sulfur co-doped porous carbon-based supercapacitor electrode material of sodium lignosulfonate / chitosan as described in claim 1, characterized in that, The sodium lignosulfonate solution is an aqueous solution of sodium lignosulfonate with a concentration of 0.3~0.6 g / ml.
3. The preparation method of the nitrogen- and sulfur co-doped porous carbon-based supercapacitor electrode material of sodium lignosulfonate / chitosan as described in claim 1, characterized in that, The chitosan solution is an acetic acid solution of chitosan with a concentration of 0.3~0.6 g / ml.
4. The preparation method of the nitrogen- and sulfur co-doped porous carbon-based supercapacitor electrode material of sodium lignosulfonate / chitosan as described in claim 1, characterized in that, The carbonization conditions are: temperature 750~800℃, holding time 1~2h.
5. The preparation method of the nitrogen- and sulfur co-doped porous carbon-based supercapacitor electrode material of sodium lignosulfonate / chitosan as described in claim 1, characterized in that, The carbonization is carried out under nitrogen protection, with a heating rate of 5-8°C / min. -1 .
6. The method for preparing the nitrogen- and sulfur-co-doped porous carbon-based supercapacitor electrode material of sodium lignosulfonate / chitosan as described in claim 1, characterized in that, The pickling is performed using a hydrochloric acid solution with a concentration of 1~1.5 mol / L. -1 ; Alternatively, the drying process may be vacuum drying at a temperature of 80-85°C.
7. The sodium lignosulfonate / chitosan highly mesoporous nitrogen and sulfur co-doped porous carbon-based supercapacitor electrode material prepared by the method according to any one of claims 1-6.
8. The application of the sodium lignosulfonate / chitosan highly mesoporous nitrogen and sulfur co-doped porous carbon-based supercapacitor electrode material according to claim 7 in the preparation of supercapacitors.
Citation Information
Patent Citations
Preparation method of high-performance nitrogen-doped biomass porous carbon for supercapacitor
CN109767927A
Method for preparing mesopore-enriched graded porous carbon material for supercapacitor
CN110862077A
Method for generating graded porous carbon based on biomass derivative self-assembly and application thereof
CN115285991A
Nanosphere materials and methods of synthesizing same
WO2020149755A2
KR1019662290000B1
